The National SOM Survey 1997 - SOM Institute, University of Gothenburg (University of Gothenburg, 2011)
Since 1986 the research project ´Samhälle Opinion Massmedia´ (SOM) has been carrying out an annual nation-wide survey of Swedish opinions. This is accordingly the twelfth survey in this series. The questionnaire was divided into six subject fields: mass media; politics and society; Sweden´s relations to the rest of the world; energy, nuclear power and environment; leisure, media and public issues; and background. Most of the questions are replications of questions asked in one or several previous SOM-surveys. New media questions dealt with newspaper reading on the internet. The respondents also had to state if they agreed or not with a number of statements concerning morning paper usage. Respondents were also asked about the Swedish EU-membership and the effect of the membership on different areas. A number of questions dealt with the respondent´s willingness to pay more taxes if the money was used for environmental issues. New questions on media habits included: how often the respondent watched different programs on television; the reliability of different programs; reasons to watch different types of television programs; and opinions on a number of television personalities. The respondent also had to value how important a number of things are for a modern society to work properly. Furthermore there were questions about membership in religious denominations, geographical identity, domestic animals, media equipment mainly used by the respondent, and internet usage.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den tolfte undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

1997 års undersökning består av sju sammanhållna delar: massmedier; politik och samhälle; Sverige och omvärlden; energi, kärnkraft och miljö; hälsorisker; fritid, media och samhällsfrågor; samt bakgrundsfrågor. Genom att frågor ställts på ett likartat sätt över tid finns det i SOM-serien tidsserier om bland annat medieanvändning, politik, kärnkraftsopinion och förtroende för olika samhällsinstitutioner och grupper.

Nya frågeställningar i denna undersökning behandlar bland annat: internetanvändning; det svenska EU-medlemskapet och dess inverkan på ett antal områden; beredskap att betala mera i skatt om pengarna används för miljöändamål. Nya frågor om medievanor inkluderar: hur ofta man tittar på olika tv-program; trovärdigheten hos ett antal tv-program; orsak att se på olika typer av tv-program; och åsikt om ett antal tv-personligheter. Respondenten fick också ange betydelsen av ett antal saker för att ett modernt samhälle skall fungera. Därutöver ingick även ett antal nya frågor om medlemskap i religiösa organisationer, geografisk identitet, husdjur, medieutrustning i hushållet som huvudsakligen används av respondenten, samt internetanvändning.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 1997
Riks-SOM 1997
Keywords: mass media; massmedia; population migration; migration; participation; deltagande; energy; energi; local government services; kommunal service; nuclear energy; kärnkraft; news; nyheter; internal politics; inrikespolitik; visits to recreational facilities; fritidsanläggningsbesök; political parties; politiska partier; political leaders; politiska ledare; citizen participation; medborgardeltagande; leisure time activities; fritidsaktiviteter; mass media use; mediaanvändning; radio listening; radiolyssnande; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap